A preparation method and product of a transition metal carbon-nitrogen bifunctional catalyst and its application

By adopting the preparation method of the dual-function catalyst of the transition metal carbon nitrogen, the ZiF-Cozn (3: 1) front drive and nitrate are used to synthesize the problem of high metal catalysts, low reserves, and poor durability. Water catalytic performance, replace the application of precious metal catalysts.

CN118950066BActive Publication Date: 2025-01-24CHANGZHOU HYDROGEN FLOW TECH NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411427398.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-24
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The precious metal catalysts used in the existing electrolytic hydrogen production technology are high in price, small reserves and poor durability, which limits the large-scale application of electrolytic hydrogen production technology.

Method used

The preparation method of the transition metal carbon nitrogen dual-function catalyst is used to use ZiF-Cozn (3: 1) as the front drive through the water bathing method, and the nitrate nitrate as auxiliary regulatory synthesis to make catalysts with excellent electrolytic water catalytic performance.

Benefits of technology

This catalyst can effectively regulate the size and surface activity site of metal nanoparticles, improve the chemical environment around the activated site, improve the activation ability of catalysts, achieve excellent electrolytic water catalytic performance, and replace the application of precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118950066B_ABST
    Figure CN118950066B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and product of a transition metal carbon-nitrogen bifunctional catalyst and its application, and relates to the technical field of catalyst preparation, including adding cobalt nitrate, zinc nitrate and hexadecyl trimethyl ammonium bromide to deionized water to obtain a mixed aqueous solution; the mixed aqueous solution is added dropwise to a 2-methylimidazole aqueous solution, stirred, heated in a water bath and stirred, the resulting product is washed, centrifuged, and freeze-dried to obtain a purple powder ZIF-CoZn precursor; KNO3 powder and ZIF-CoZn precursor are fully ground, heat-insulated and calcined under N2 atmosphere, and the obtained black solid powder is washed and centrifuged to obtain a catalyst. The present invention uses nitrate as an auxiliary catalyst for regulating and synthesizing excellent performance, can effectively regulate the size of metal nanoparticles to increase surface active sites, plays a role in efficiently activating the catalyst, and gives the catalyst excellent electrolytic water catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalyst preparation, and specifically relates to a preparation method and product of a transition metal carbon-nitrogen dual-function catalyst and application thereof. Background Art

[0002] Sustainable energy is often limited by time and space and requires energy storage equipment for subsequent use. Therefore, in the post-fossil fuel era, hydrogen (H2) as a clean and environmentally friendly energy carrier has received great attention and has been extensively studied. At present, hydrogen can be extracted from water by decomposing water through electrolysis, that is, electrolysis of water to produce hydrogen. This process has little impact on the environment and water resources are extremely abundant. Even the by-product oxygen has almost no negative impact on the environment, and oxygen is also an important production raw material. Therefore, electrolysis of water to produce hydrogen is an important technology for producing "green hydrogen". At present, hydrogen produced by full water decomposition accounts for only about 4% of the total hydrogen production, which is closely related to its high energy consumption (considerable energy is required in the process of breaking the hydrogen bonds in water molecules).

[0003] The reaction in the water electrolysis process includes two half reactions at the anode and cathode: oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Both HER and OER are kinetic reactions. In the actual water electrolysis process, catalysts must be used at the anode and cathode to prevent the strong chemical bonds between O and H in the water molecules. Only in this way can the whole process be accelerated.

[0004] Currently, the catalysts used for water electrolysis are generally precious metals (Ir, Ru, Pt, etc.). Although precious metal catalysts have higher HER or OER catalytic performance, they inevitably have disadvantages such as high price, small reserves, and poor durability, which restrict the large-scale application of water electrolysis hydrogen production technology. Summary of the invention

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a transition metal carbon-nitrogen bifunctional catalyst.

[0007] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a transition metal carbon-nitrogen bifunctional catalyst, comprising:

[0008] Adding cobalt nitrate, zinc nitrate and hexadecyltrimethylammonium bromide into deionized water to prepare a mixed aqueous solution;

[0009] The mixed aqueous solution was added dropwise to the 2-methylimidazole aqueous solution, stirred for 30-60 min, heated in a water bath and stirred for 2-4 h, and the obtained product was washed, centrifuged, and freeze-dried to obtain a purple powder, which is the ZIF-CoZn precursor;

[0010] The KNO3 powder and the ZIF-CoZn precursor are fully ground, moved into a tube furnace, and calcined under a N2 atmosphere. The obtained black solid powder is washed with ultrapure water and anhydrous ethanol and centrifuged to obtain the transition metal carbon-nitrogen bifunctional catalyst.

[0011] Wherein, the ratio of the KNO3 powder to the ZIF-CoZn precursor is 0.01~0.025g:1g.

[0012] As a preferred embodiment of the preparation method of the present invention, cobalt nitrate, zinc nitrate and hexadecyltrimethylammonium bromide are added into deionized water, wherein the ratio of cobalt nitrate, zinc nitrate and hexadecyltrimethylammonium bromide is 0.03 mol:0.01 mol:0.004 mol, and the ratio of zinc nitrate and deionized water is 0.01 mol:500 mL.

[0013] As a preferred embodiment of the preparation method of the present invention, the preparation method of the 2-methylimidazole aqueous solution comprises:

[0014] 2-methylimidazole was mixed with deionized water to prepare a dimethylimidazole mixed aqueous solution, wherein the ratio of 2-methylimidazole to deionized water was 0.24 mol:500 mL.

[0015] As a preferred embodiment of the preparation method of the present invention, the mixed aqueous solution is added dropwise to the aqueous solution of 2-methylimidazole, wherein the volume ratio of the mixed aqueous solution to the aqueous solution of 2-methylimidazole is 4:1.

[0016] As a preferred embodiment of the preparation method of the present invention, the calcination is carried out under a N2 atmosphere, wherein the calcination heating rate is 5°C min -1 The calcination temperature is 800℃ and the calcination time is 2~2.5 h.

[0017] Another object of the present invention is to overcome the deficiencies in the prior art and provide a transition metal carbon nitrogen bifunctional catalyst prepared by a method for preparing a transition metal carbon nitrogen bifunctional catalyst.

[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a transition metal carbon-nitrogen bifunctional catalyst for use in electrochemical water hydrogen production.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention provides a method for preparing a transition metal carbon-nitrogen bifunctional full hydrolysis catalyst, which is prepared by a water bath calcination method using ZIF-CoZn (3:1) (the molar ratio of Co to Zn is 3:1) as a precursor and using nitrate as an auxiliary control. The catalyst has excellent performance and can effectively control the size of metal nanoparticles to increase the surface active sites and improve the chemical environment around the active sites, thereby playing a role in efficiently activating the catalyst and giving the catalyst excellent electrolytic water catalytic performance.

[0021] (2) Precious metals are rare and expensive in nature. In comparison, non-precious transition metals such as zinc, iron, and chromium, which are used as raw materials, are relatively cheap and abundant. Transition metal-nitrogen-carbon materials have excellent physical and chemical properties and platinum-like catalytic properties, making them ideal candidates to replace precious metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0023] Figure 1 HER LSV curve of Co@NC-nKNO3 in 1 M KOH in an embodiment of the present invention, wherein n=0, 0.01, 0.025, 0.05, 0.1, 0.2.

[0024] Figure 2 : These are the OER LSV curves of Co@NC-nKNO3 in 1 M KOH in an embodiment of the present invention, where n=0, 0.01, 0.025, 0.05, 0.1, and 0.2.

[0025] Figure 3 TEM morphology and microstructure of Co@NC-0.025KNO3 in the embodiment of the present invention.

[0026] Figure 4 This is the TEM image of Co@NC-0.01KNO3 in the embodiment of the present invention.

[0027] Figure 5 This is the contact angle diagram of Co@NC-0.025KNO3 in the embodiment of the present invention.

[0028] Figure 6 This is a graph showing the change in the average contact angle of Co@NC-nKNO3 with the amount of KNO3 input in an embodiment of the present invention, where n=0, 0.01, 0.025, 0.05, 0.1, 0.2. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] Evaluation of electrochemical water splitting performance: tested by PINE electrochemical workstation (Hong Kong R&D Co., Ltd.);

[0033] In the three-electrode system, the working electrode is a carbon paper loaded with a catalyst, the reference electrode is an Ag / AgCl electrode, and the counter electrode is a carbon rod; wherein the three-electrode system is used to study the two half reactions of water electrolysis, including a reduction reaction at the cathode to produce hydrogen and an oxidation reaction at the anode to produce oxygen. The present invention uses a three-electrode electrochemical device to study the catalytic activity of the catalyst;

[0034] The device was tested at room temperature and pressure with 1 M KOH as the electrolyte;

[0035] The HER and OER performances were tested in a suitable potential range (0 V to -0.7 V) by linear sweep voltammetry (LSV). At the same time, in order to test the hydrogen evolution (HER) and oxygen evolution (OER) performances of the catalyst, a current density of 10 / 500 mA cm based on the macroscopic area of ​​the electrode was used. -2 As an indicator for evaluating the catalytic activity of the catalyst;

[0036] The specific process for preparing the working electrode of the catalyst-loaded carbon paper in the embodiment of the present invention is as follows:

[0037] First, 8 mg of catalyst and 8 mg of carbon black were placed in a 3 mL sample tube, 0.9 mL of anhydrous ethanol and 100 μL of Nafion solution were added, and the mixture was shaken evenly with a vortex mixer, and ultrasonicated for 90 min in an ice bath until the solution was uniform to obtain the catalyst suspension.

[0038] Take 7.5 μL of the suspension and drop it onto the surface of the hydrophobic carbon paper (loading amount is 0.24 mg cm -2 ), and dried in the shade at room temperature to obtain a catalyst-loaded carbon paper working electrode.

[0039] The raw materials used in the embodiments of the present invention are all common commercially available products.

[0040] Example 1

[0041] (1) Add 0.03 mol of cobalt nitrate, 0.01 mol of zinc nitrate and 0.004 mol of hexadecyltrimethylammonium bromide into 500 mL of deionized water and stir well to prepare a mixed aqueous solution;

[0042] (2) Mix 0.24 mol of 2-methylimidazole with 500 mL of deionized water to prepare a dimethylimidazole mixed aqueous solution;

[0043] (3) Add 400 mL of the mixed aqueous solution dropwise to 100 mL of the 2-methylimidazole aqueous solution. After the addition is completed, continue stirring at 310 rpm for 30 min at room temperature of 25 °C. Place in a water bath and stir at 80 °C and 400 rpm for 4 h.

[0044] The obtained ZIF-CoZn precursor was washed with ultrapure water and anhydrous ethanol and centrifuged (centrifugal speed 10000rpm, centrifugal time 10min) three times, and then freeze-dried (vacuum degree 10 Pa, temperature minus 50°C, time 24h) to obtain a purple powder, namely the ZIF-CoZn precursor.

[0045] (4) Take 0.025 g KNO3 powder and 1 g ZIF-CoZn precursor, grind them thoroughly and move them into a tube furnace. -1 The temperature was raised to 800 °C at a heating rate and kept at this temperature for 2.5 h;

[0046] The obtained black solid powder was washed alternately with ultrapure water and anhydrous ethanol by centrifugation 4 times;

[0047] After drying, the catalyst was obtained and named as Co@NC-0.025KNO3.

[0048] The TEM morphology and microstructure of Co@NC-0.025KNO3 can be found in Figure 3 It can be observed that a large number of carbon nanotubes extend from the surface of the carbon nanoblocks; there are abundant interconnected mesopores in the carbon nanoblocks, and many nanoparticles are embedded in them or coated in the carbon nanotubes. This nanostructure can effectively prevent the aggregation and shedding of nanoparticles and improve the durability of the catalyst during the reaction.

[0049] The hydrophilicity and hydrophobicity of the catalyst surface will affect the desorption characteristics of H2 and O2 from the surface during water electrolysis, and thus affect the HER / OER performance. Figure 5 The contact angle graph of Co@NC-0.025KNO3 is shown, and the average contact angle is ~59.6°.

[0050] (3) The above catalysts were prepared into working electrodes for electrochemical water splitting tests

[0051] For HER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials of the current densities are 87 / 293 mV, respectively.

[0052] For OER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials for the current densities are 380 / 516 mV, respectively.

[0053] Example 2

[0054] (1) Add 0.03 mol of cobalt nitrate, 0.01 mol of zinc nitrate and 0.004 mol of hexadecyltrimethylammonium bromide into 500 mL of deionized water and stir well to prepare a mixed aqueous solution;

[0055] (2) Mix 0.24 mol of 2-methylimidazole with 500 mL of deionized water to prepare a dimethylimidazole mixed aqueous solution;

[0056] (3) Add 400 mL of the mixed aqueous solution dropwise to 100 mL of the 2-methylimidazole aqueous solution. After the addition is completed, continue stirring at 310 rpm for 30 min at room temperature of 25 °C. Place in a water bath and stir at 80 °C and 400 rpm for 4 h.

[0057] The obtained ZIF-CoZn precursor was washed with ultrapure water and anhydrous ethanol respectively, centrifuged (centrifugal speed 10000rpm, centrifugal time 10min) 3 times, and freeze-dried (vacuum degree 10 Pa, temperature minus 50°C, time 24h) to obtain a purple powder, namely the ZIF-CoZn precursor.

[0058] (4) Take 0.01g KNO3 powder and 1g ZIF-CoZn (3:1) precursor and grind them thoroughly. Then move them into a tube furnace and heat them at 5℃min in N2 atmosphere. -1 The temperature was raised to 800℃ at a rate of 1.5°C and kept at this temperature for 2.5 h;

[0059] The obtained black solid powder was washed alternately with ultrapure water and anhydrous ethanol by centrifugation 4 times;

[0060] After drying, the catalyst was obtained and named Co@NC-0.01KNO3. The TEM image of Co@NC-0.01KNO3 can be found in Figure 4 It can be seen that with the gradual increase of KNO3 input, the density of Co nanoparticles on the carbon nanosubstrate also decreases.

[0061] (3) The above catalysts were prepared into working electrodes for electrochemical water splitting tests

[0062] For HER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials for the current densities are 160 / 499 mV, respectively.

[0063] For OER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials of the current densities are 439 / 570 mV, respectively.

[0064] Example 3

[0065] (1) Preparation of precursor: A mixed aqueous solution of cobalt nitrate (0.03 mol), zinc nitrate (0.01 mol) and hexadecyltrimethylammonium bromide (0.004 mol) was added dropwise to an aqueous solution of 2-methylimidazole (0.24 mol). After the addition was completed, the mixture was stirred at room temperature (25°C) for 30 min (310 rpm), and then heated in a water bath (80°C) and stirred (400 rpm) for 4 h.

[0066] The obtained ZIF-CoZn precursor was washed (washed with ultrapure water and anhydrous ethanol) and centrifuged (centrifugal speed 10000 rpm, centrifugal time 10 min) three times, and then freeze-dried (vacuum degree 10 Pa, temperature minus 50°C) to obtain a purple powder for use.

[0067] (2) Take 0.05 g KNO3 powder and 1 g ZIF-CoZn (3:1) precursor and grind them thoroughly. Then move them into a tube furnace and heat them at 5 °C min-1 under N2 atmosphere. -1 The temperature was raised to 800℃ at a rate of 1.5°C and kept at this temperature for 2.5 h;

[0068] The obtained black solid powder was washed and centrifuged several times alternately with ultrapure water and anhydrous ethanol;

[0069] After drying, the catalyst was obtained and named as Co@NC-0.05KNO3.

[0070] (3) The above catalysts were prepared into working electrodes for electrochemical water splitting tests

[0071] For HER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials of the current density are 108 / 396 mV;

[0072] For OER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials for the current densities are 400 / 541 mV, respectively.

[0073] Example 4

[0074] (1) Add 0.03 mol of cobalt nitrate, 0.01 mol of zinc nitrate and 0.004 mol of hexadecyltrimethylammonium bromide into 500 mL of deionized water and stir well to prepare a mixed aqueous solution;

[0075] (2) Mix 0.24 mol of 2-methylimidazole with 500 mL of deionized water to prepare a dimethylimidazole mixed aqueous solution;

[0076] (3) Add 400 mL of the mixed aqueous solution dropwise to 100 mL of the 2-methylimidazole aqueous solution. After the addition is completed, continue stirring at 310 rpm for 30 min at room temperature of 25 °C. Place in a water bath and stir at 80 °C and 400 rpm for 4 h.

[0077] The obtained ZIF-CoZn precursor was washed with ultrapure water and anhydrous ethanol respectively, centrifuged (centrifugal speed 10000rpm, centrifugal time 10min) 3 times, and freeze-dried (vacuum degree 10 Pa, temperature minus 50°C, time 24h) to obtain a purple powder, namely the ZIF-CoZn precursor.

[0078] (4) Take 0.1 g KNO3 powder and 1 g ZIF-CoZn (3:1) precursor and grind them thoroughly. Then move them into a tube furnace and heat them at 5 °C min-1 under N2 atmosphere. -1 The temperature was raised to 800℃ at a rate of 1.5°C and kept at this temperature for 2.5 h;

[0079] The obtained black solid powder was washed and centrifuged several times alternately with ultrapure water and anhydrous ethanol;

[0080] After drying, the catalyst was obtained and named as Co@NC-0.1KNO3.

[0081] (3) The above catalysts were prepared into working electrodes for electrochemical water splitting tests

[0082] For HER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2The overpotentials of the current densities are 224 / 531 mV, respectively.

[0083] For OER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials of the current densities are 471 / 628 mV, respectively.

[0084] Example 5

[0085] (1) Add 0.03 mol of cobalt nitrate, 0.01 mol of zinc nitrate and 0.004 mol of hexadecyltrimethylammonium bromide into 500 mL of deionized water and stir well to prepare a mixed aqueous solution;

[0086] (2) Mix 0.24 mol of 2-methylimidazole with 500 mL of deionized water to prepare a dimethylimidazole mixed aqueous solution;

[0087] (3) Add 400 mL of the mixed aqueous solution dropwise to 100 mL of the 2-methylimidazole aqueous solution. After the addition is completed, continue stirring at 310 rpm for 30 min at room temperature of 25 °C. Place in a water bath and stir at 80 °C and 400 rpm for 4 h.

[0088] The obtained ZIF-CoZn precursor was washed with ultrapure water and anhydrous ethanol respectively, centrifuged (centrifugal speed 10000rpm, centrifugal time 10min) 3 times, and freeze-dried (vacuum degree 10 Pa, temperature minus 50°C, time 24h) to obtain a purple powder, namely the ZIF-CoZn precursor.

[0089] (4) Take 0.2 g KNO3 powder and 1 g ZIF-CoZn (3:1) precursor and grind them thoroughly. Then move them into a tube furnace and heat them at 5 °C min under N2 atmosphere. -1 The temperature was raised to 800℃ at a rate of 1.5°C and kept at this temperature for 2.5 h;

[0090] The obtained black solid powder was washed and centrifuged several times alternately with ultrapure water and anhydrous ethanol;

[0091] After drying, the catalyst was obtained and named as Co@NC-0.2KNO3.

[0092] (5) The above catalyst was prepared into a working electrode for electrochemical water splitting test

[0093] For HER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials for the current densities are 260 / 557 mV, respectively.

[0094] For OER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials of the current densities are 487 / 663 mV, respectively.

[0095] Comparative Example 1

[0096] (1) Add 0.03 mol of cobalt nitrate, 0.01 mol of zinc nitrate and 0.004 mol of hexadecyltrimethylammonium bromide into 500 mL of deionized water and stir well to prepare a mixed aqueous solution;

[0097] (2) Mix 0.24 mol of 2-methylimidazole with 500 mL of deionized water to prepare a dimethylimidazole mixed aqueous solution;

[0098] (3) Add 400 mL of the mixed aqueous solution dropwise to 100 mL of the 2-methylimidazole aqueous solution. After the addition is completed, continue stirring at 310 rpm for 30 min at room temperature of 25 °C. Place in a water bath and stir at 80 °C and 400 rpm for 4 h.

[0099] The obtained ZIF-CoZn precursor was washed with ultrapure water and anhydrous ethanol respectively, centrifuged (centrifugal speed 10000rpm, centrifugal time 10min) 3 times, and freeze-dried (vacuum degree 10 Pa, temperature minus 50°C, time 24h) to obtain a purple powder, namely the ZIF-CoZn precursor.

[0100] (4) Take 1 g of ZIF-CoZn (3:1) precursor and grind it thoroughly before moving it into a tube furnace. -1 The temperature was raised to 800℃ at a rate of 1.5°C and kept at this temperature for 2.5 h;

[0101] The obtained black solid powder was washed and centrifuged several times alternately with ultrapure water and anhydrous ethanol;

[0102] (5) The above catalyst was prepared into a working electrode for electrochemical water splitting test

[0103] For HER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials of the current densities are 243 / 617 mV, respectively.

[0104] For OER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials for the current densities are 435 / 700 mV, respectively.

[0105] The HER LSV curves of the catalysts prepared in Examples 1 to 5 and Comparative Example 1 in 1 M KOH are shown in Figure 1 Among them, Pt / C is the control group, which uses 20% Pt / C as the raw material to make the working electrode. The 20 wt% Pt / C catalyst is carbon as the carrier, and the loading mass of platinum on carbon is 20%. It was purchased from Thermo Fisher, with a specific surface area of ​​103~112 m 2 / g, the preparation process of the working electrode is:

[0106] 8 mg of metal catalyst 20% Pt / C and 8 mg of carbon black were placed in a 3 mL sample tube, 0.9 mL of anhydrous ethanol and 100 μL of Nafion solution were added, and the mixture was shaken evenly with a vortex mixer, and ultrasonicated for 90 min in an ice bath until the solution was uniform to obtain the catalyst suspension;

[0107] Take 7.5 μL of the suspension and drop it onto the surface of the hydrophobic carbon paper (loading amount is 0.24 mg cm -2 ), and dried in the shade at room temperature to obtain a catalyst-loaded carbon paper working electrode.

[0108] It can be seen that according to η 10 -HER, the catalytic performance of these catalysts is as follows: Co@NC-0.025KNO3>Co@NC-0.05KNO3>Co@NC-0.01KNO3>Co@NC>Co@NC-0.1KNO3>Co@NC-0.2KNO3; according to η 500 -HER and η 1000 -HER, the order of catalytic performance is: Co@NC-0.025KNO3>Co@NC-0.05KNO3>Co@NC-0.01KNO3>Co@NC-0.1KNO3>Co@NC-0.2KNO3>Co@NC.

[0109] The OER LSV curves of the catalysts prepared in Examples 1 to 5 and Comparative Example 1 in 1 M KOH are shown in Figure 2 , wherein IrO2 is a control group, in which the working electrode is prepared by using the metal catalyst IrO2, the metal catalyst IrO2 is purchased from Thermo Fisher, the product number is A17849, and the preparation process of the working electrode is:

[0110] 8 mg of metal catalyst IrO2 and 8 mg of carbon black were placed in a 3 mL sample tube, 0.9 mL of anhydrous ethanol and 100 μL of Nafion solution were added, and the mixture was shaken evenly with a vortex mixer, and ultrasonicated for 90 min in an ice bath until the solution was uniform to obtain the catalyst suspension.

[0111] Take 7.5 μL of the suspension and drop it onto the surface of the hydrophobic carbon paper (loading amount is 0.24 mg cm -2 ), and dried in the shade at room temperature to obtain a catalyst-loaded carbon paper working electrode.

[0112] It can be seen that after KNO3-assisted calcination, the OER catalytic performance of the obtained catalyst was optimized, especially in the high current density region; 10 Taking η as an indicator (taking Co@NC into account), the order of OER catalytic performance is: Co@NC-0.025KNO3>Co@NC-0.05KNO3>Co@NC>Co@NC-0.01KNO3>Co@NC-0.1KNO3>Co@NC-0.2KNO3; 500 Based on the indicators, the order of OER catalytic performance is: Co@NC-0.025KNO3>Co@NC-0.05KNO3>Co@NC-0.01KNO3>Co@NC-0.1KNO3>Co@NC-0.2KNO3>Co@NC.

[0113] For the variation of the average contact angle of Co@NC-nKNO3 with the amount of KNO3 input, see Figure 6 , where n=0, 0.01, 0.025, 0.05, 0.1, 0.2. It can be seen that it presents an "inverted V-shaped" pattern; overall, the average contact angle ranges from ~47° to ~129.6°; when no KNO3 is added, the average contact angle of Co@NC is ~88.2°, which has a certain hydrophobicity (the contact angle is greater than 90°, and the surface is hydrophobic); when a small amount of KNO3 (0.025 g) is added, the average contact angle is significantly reduced to ~59.6°; in other words, The surface of Co@NC-0.025KNO3 has a high hydrophilicity (the contact angle is less than 90°, and the surface is hydrophilic); when the input amount of KNO3 is continuously increased, the average contact angle exceeds 90° and slowly increases, and the surface becomes more hydrophobic; for an excellent HER / OER catalyst, a higher surface hydrophilicity is conducive to the desorption of H2 and O2, and thus to the performance of the intrinsic performance of HER / OER; it can be seen that Co@NC-0.025KNO3 should have good HER / OER performance.

[0114] Comparative Example 2

[0115] (1) Add 0.03 mol of cobalt nitrate, 0.01 mol of zinc nitrate and 0.004 mol of hexadecyltrimethylammonium bromide into 500 mL of deionized water and stir well to prepare a mixed aqueous solution;

[0116] (2) Mix 0.24 mol of 2-methylimidazole with 500 mL of deionized water to prepare a dimethylimidazole mixed aqueous solution;

[0117] (3) Add 400 mL of the mixed aqueous solution dropwise to 100 mL of the 2-methylimidazole aqueous solution. After the addition is completed, continue stirring at 310 rpm for 30 min at room temperature of 25 °C. Place in a water bath and stir at 80 °C and 400 rpm for 4 h.

[0118] The obtained ZIF-CoZn precursor was washed with ultrapure water and anhydrous ethanol respectively, centrifuged (centrifugal speed 10000rpm, centrifugal time 10min) 3 times, and freeze-dried (vacuum degree 10 Pa, temperature minus 50°C, time 24h) to obtain a purple powder, namely the ZIF-CoZn precursor.

[0119] (4) Take 0.025 g K2CO3 powder and 1 g ZIF-CoZn (3:1) precursor and grind them thoroughly. Then move them into a tube furnace and heat them at 5 °C min-1 under N2 atmosphere. -1 The temperature was raised to 800℃ at a rate of 1.5°C and kept at this temperature for 2.5 h;

[0120] The obtained black solid powder was washed and centrifuged several times alternately with ultrapure water and anhydrous ethanol;

[0121] (5) The above catalyst was prepared into a working electrode for electrochemical water splitting test

[0122] For HER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials for the current densities are 280 / 675 mV, respectively.

[0123] For OER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials for the current densities are 460 / 750 mV, respectively.

[0124] Comparative Example 3

[0125] (1) Add 0.05 mol of cobalt nitrate, 0.01 mol of zinc nitrate and 0.004 mol of hexadecyltrimethylammonium bromide into 500 mL of deionized water and stir well to prepare a mixed aqueous solution;

[0126] (2) Mix 0.24 mol of 2-methylimidazole with 500 mL of deionized water to prepare a dimethylimidazole mixed aqueous solution;

[0127] (3) Add 400 mL of the mixed aqueous solution dropwise to 100 mL of the 2-methylimidazole aqueous solution. After the addition is completed, continue stirring at 310 rpm for 30 min at room temperature of 25 °C. Place in a water bath and stir at 80 °C and 400 rpm for 4 h.

[0128] The obtained ZIF-CoZn precursor was washed with ultrapure water and anhydrous ethanol respectively, centrifuged three times, and freeze-dried (vacuum degree 10 Pa, temperature minus 50°C, time 24h) to obtain a purple powder, namely the ZIF-CoZn precursor.

[0129] (4) Take 0.025 g KNO3 powder and 1 g ZIF-CoZn precursor, grind them thoroughly and move them into a tube furnace. -1 The temperature was raised to 800℃ at a rate of 1.5°C and kept at this temperature for 2.5 h;

[0130] The obtained black solid powder was washed alternately with ultrapure water and anhydrous ethanol and centrifuged (centrifugal speed 10000 rpm, centrifugal time 10 min) 4 times; after drying, the catalyst was obtained.

[0131] (5) The above catalyst was prepared into a working electrode for electrochemical water splitting test

[0132] For HER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials for the current densities are 180 / 330 mV, respectively.

[0133] For OER, the catalyst drove 10 / 500 mA cm in 1 M KOH electrolyte. -2 The overpotentials for the current densities are 400 / 620 mV, respectively.

[0134] In summary, the present invention provides a method for preparing a transition metal carbon-nitrogen bifunctional full hydrolysis catalyst, which uses ZIF-CoZn (3:1) as a precursor through a water bath calcination method and uses nitrate as an auxiliary regulation to synthesize a catalyst with excellent performance. It can effectively regulate the size of metal nanoparticles to increase surface active sites and improve the chemical environment around the active sites, thereby playing a role in efficiently activating the catalyst and giving the catalyst excellent electrolytic water catalytic performance.

[0135] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a transition metal carbon-nitrogen bifunctional catalyst, characterized in that: include, Adding cobalt nitrate, zinc nitrate and hexadecyltrimethylammonium bromide into deionized water to prepare a mixed aqueous solution; The mixed aqueous solution was added dropwise to the 2-methylimidazole aqueous solution, stirred for 30 to 60 minutes, heated in a water bath and stirred for 2 to 4 hours, and the obtained product was washed, centrifuged, and freeze-dried to obtain a purple powder, which is a ZIF-CoZn precursor, wherein the molar ratio of Co to Zn in the ZIF-CoZn precursor is 3:1; The KNO3 powder and the ZIF-CoZn precursor are fully ground, moved into a tube furnace, and calcined under a N2 atmosphere. The obtained black solid powder is washed with ultrapure water and anhydrous ethanol and centrifuged to obtain the transition metal carbon-nitrogen bifunctional catalyst. The calcination heating rate is 5℃min -1 , the calcination temperature is 800℃, and the calcination time is 2~2.5 h; Wherein, the ratio of the KNO3 powder to the ZIF-CoZn precursor is 0.01~0.025g:1g.

2. The preparation method according to claim 1, characterized in that: The cobalt nitrate, zinc nitrate and hexadecyltrimethylammonium bromide are added into deionized water, wherein the ratio of the cobalt nitrate, zinc nitrate and hexadecyltrimethylammonium bromide is 0.03 mol:0.01 mol:0.004 mol, and the ratio of the zinc nitrate and deionized water is 0.01 mol:500 mL.

3. The preparation method according to claim 1, characterized in that: The 2-methylimidazole aqueous solution, the preparation method thereof comprises: 2-methylimidazole was mixed with deionized water to prepare a dimethylimidazole mixed aqueous solution, wherein the ratio of 2-methylimidazole to deionized water was 0.24 mol:500 mL.

4. The preparation method according to claim 1 or 3, characterized in that: The mixed aqueous solution is added dropwise to the aqueous solution of 2-methylimidazole, wherein the volume ratio of the mixed aqueous solution to the aqueous solution of 2-methylimidazole is 4:

1.

5. A transition metal carbon-nitrogen bifunctional catalyst prepared by the preparation method described in any one of claims 1 to 4.

6. Use of the transition metal carbon-nitrogen bifunctional catalyst according to claim 5 in electrochemical water hydrogen production.

Citation Information

Patent Citations

  • Preparation method of transition group metal / carbon pipe / graphene electrocatalyst for hydrogen evolution reaction

    CN108385124A

  • Secondary battery and preparation method thereof

    CN108470908A